2014
DOI: 10.5430/ijba.v6n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of an MBA Program Capstone Project Assessment Measure for AACSB Accreditation

Abstract: There is very little written about assessment measures business schools use for assessing their programs that not only helps them meet the assessment criteria necessary for AACSB accreditation but also helps them improve the curriculum to build top-tier successful programs. This paper informs the literature on the assessment measure (and process) used by an MBA program to assess student learning through end-of-program capstone projects; success that is demonstrated by stabilized enrollments and a recent top-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
1
Order By: Relevance
“…After another failed attempt assessing two different SLOs (through another poorly chosen assignment), we decided that graduate students could best show their mastery of the program by assessing student learning from the Capstone paper they completed in their final course in the program. In fact, we found that others were successful using Capstone projects in this way as well (Gray, Boasson, Carson, and Chakraborty 2014; van Acker and Bailey 2011). Therefore, beginning in spring 2015, we assessed all seven SLOs using students' Capstone papers.…”
Section: Lesson 1: Choose Your Assignment Carefullymentioning
confidence: 81%
“…After another failed attempt assessing two different SLOs (through another poorly chosen assignment), we decided that graduate students could best show their mastery of the program by assessing student learning from the Capstone paper they completed in their final course in the program. In fact, we found that others were successful using Capstone projects in this way as well (Gray, Boasson, Carson, and Chakraborty 2014; van Acker and Bailey 2011). Therefore, beginning in spring 2015, we assessed all seven SLOs using students' Capstone papers.…”
Section: Lesson 1: Choose Your Assignment Carefullymentioning
confidence: 81%
“…Un ejercicio de revisión del uso de pruebas estandarizadas (como la Major Field Test in Business, MFT-B) es el de Bielinska-Kwapisz & Brown (2014) que revisa las características de universidades acreditadas AACSB que usan o no dichas pruebas para evaluar a sus egresados en sus metas de aprendizaje. Gray, Boasson, Carson & Chakraborty (2015) presentan los resultados de evaluación de metas de aprendizaje de un MBA tipo, de acuerdo con los parámetros sugeridos por AACSB y tomados de Palomba & Banta (1999). Sin embargo, en ninguno de estos casos y según los mismos autores, las pruebas pueden considerarse contundentes y definitivas.…”
Section: Figura 1 Comparación De Estándares Entre Aacsb and Equisunclassified
“…Comprehensive exams and capstone projects are instruments used in the third approach of AoL, which provide summative data on students learning upon the completion of the program. The College of Business did not consider using the third approach, although capstone projects can be successfully used to access the learning outcomes of the MBA programs as Gray, Boasson, Carson and Chakraborty (2015) pointed out. They wrote that, "These summative assessments are to provide stakeholders such as faculty and administrators with a snap shot of students learning as a result of a culminating course experiences within the programs.…”
Section: The Case Of the University Of Bahrainmentioning
confidence: 99%